Left main coronary angioplasty A case report (University Heart Journal, 2009)
A 52 years lady presented with chest pain and shortness of breath. Chest pain was initially CCS class II and gradually CCS class III. Coronary angiogram reveals triple vessel disease for which she underwent CABG (RSVG to LAD) in December 1999. On January 2003 PTCA with stent (sirolimus - 3 x 15m m) to LCX was done. She again complaints of chest pain after a short symptom less period. Recent coronary angiogram revealed TVD with left main involvement. In this article we will describe a rare case of successful stenting in left main disease.   doi: 10.3329/uhj.v5i1.3441 University Heart Journal Vol. 5, No. 1, January 2009 40-41